1995
DOI: 10.1111/j.1600-0838.1995.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal plane translation of the tibia in anterior cruciate ligament‐deficient knees during commonly used rehabilitation exercises

Abstract: It may be assumed that exercises that provoke high sagittal plane knee translations also induce high stresses on an anterior cruciate ligament substitute and, therefore, these exercises should be limited during the first months after reconstruction. In 18 patients with unilateral anterior cruciate ligament deficiency, sagittal plane knee translations were measured with a goniometer linkage system during common activities. The largest translations were found during low‐speed isokinetic exercises. Further, isoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Kizuki et al 24 reported 4.1 mm more A/P translation in ACL-deficient knees relative to the uninjured knees of their subjects as they performed a nonloaded, seated 908 knee extension task in an exercise dynamometer (Biodex Medical Systems, Inc., Shirley, NY). In the above studies, tibial translation was defined as displacement relative to data collected in reference positions, such as non-loaded full extension, 22,23 or a series of values measured as the knee was passively extended. 24 Joint positioning in such reference configurations may itself be affected by pathology; for instance, fixed joint subluxations have been reported in ACL-deficient subjects during standing by Almekinders and Chiavetta.…”
Section: Discussionmentioning
confidence: 99%
“…Kizuki et al 24 reported 4.1 mm more A/P translation in ACL-deficient knees relative to the uninjured knees of their subjects as they performed a nonloaded, seated 908 knee extension task in an exercise dynamometer (Biodex Medical Systems, Inc., Shirley, NY). In the above studies, tibial translation was defined as displacement relative to data collected in reference positions, such as non-loaded full extension, 22,23 or a series of values measured as the knee was passively extended. 24 Joint positioning in such reference configurations may itself be affected by pathology; for instance, fixed joint subluxations have been reported in ACL-deficient subjects during standing by Almekinders and Chiavetta.…”
Section: Discussionmentioning
confidence: 99%
“…1). The reproducibility of this system has been reported previously [20] and it has been employed by several investigators to study characteristics of knee motion [9,17,19,21]. It is composed of femoral and tibial frames and three goniometers in a rotation module to measure the relative rotation between the femur and the tibia.…”
Section: Methodsmentioning
confidence: 99%
“…The system was zeroed with the participant lying relaxed at full knee extension and neutral knee rotation. Following previous reports [9,20,21], the alignment of the potentiometers was checked repeatedly and carefully in the zeroing screen of the computer during exercise. The protocol was repeated with fresh zeroing if values were different from the original.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations